Economics of Biodiversity Conservation in Nepal - Gotame, Bharat (The Initiation, 2010)
Nepal, a developing country has low per capita income and 2.8% economic growth rate. This simply implies higher marginal utility of income and lower willingness to pay for environmental improvements and amenities. Biodiversity has multiple benefits, but some economic obstacles like lack of appropriate market pricing, intangible nature of social benefit derived by conservation of biological resources, ownership issue, and conventional method of national income accounting, make some illusion to adopt market based biodiversity conservation approaches in developing country like Nepal. This literature review paper attempts to summarize the economic benefits of biodiversity, threats of biodiversity conservation in Nepal and some financial appraisal of biodiversity conservation of Nepal (in case of Department of National Park and Wildlife Conservation & their some field offices). In Nepal, biodiversity conservation efforts have largely been centered on protection of natural resources within Protected Areas (PA) which is not justifiable but many of naturalists are in this dilemma. The issue of ‘conservation for people' tries to enforce policy maker, PA manager and other stakeholders to carry economically sound biodiversity conservation mechanism which ultimately tends to the PA for human welfare. The provision of economic incentives either by the direct investment or by creating economic opportunities leads to the promotion of biodiversity conservation. The poorer the people lower the willingness to pay for environmental quality or amenities because of the income elasticity of environmental services. Key Words: Biodiversity conservation, Economic growth, Environmental services, Economic benefits and constraints DOI: 10.3126/init.v2i1.2524 The Initiation Vol.2(1) 2008 pp55-61